Comparative Transcriptome Analysis Reveals the Cause for Accumulation of Reactive Oxygen Species During Pollen Abortion in Cytoplasmic Male-Sterile Kenaf Line 722HA - Zhou, Bujin (Int J Mol Sci, 2019)
Cytoplasmic male sterility (CMS) is a maternally inherited trait used for hybrid production in plants, a novel kenaf CMS line 722HA was derived from the thermo-sensitive male-sterile mutant ‘HMS’ by recurrent backcrossing with 722HB. The line 722HA has great potential for hybrid breeding in kenaf. However, the underlying molecular mechanism that controls pollen abortion in 722HA remains unclear, thus limiting the full utilization of this line. To understand the possible mechanism governing pollen abortion in 722HA, cytological, transcriptomic, and biochemical analyses were carried out to compare the CMS line 722HA and its maintainer line 722HB. Cytological observations of the microspore development revealed premature degradation of the tapetum at the mononuclear stage, which resulted in pollen dysfunction. The k-means clustering analysis of differentially expressed genes (DEGs) revealed that these genes are related to processes associated with the accumulation of reactive oxygen species (ROS), including electron transport chain, F(1)F(0)-ATPase proton transport, positive regulation of superoxide dismutase (SOD), hydrogen peroxide catabolic, and oxidation-reduction. Biochemical analysis indicated that ROS-scavenging capability was lower in 722HA than in 722HB, resulting in an accumulation of excess ROS, which is consistent with the transcriptome results. Taken together, these results demonstrate that excessive ROS accumulation may affect the normal development of microspores. Our study provides new insight into the molecular mechanism of pollen abortion in 722HA and will promote further studies of kenaf hybrids.